Tinjauan Sistem Proporsional Terbuka Dalam Pemilu Legislatif 2019 Terhadap Dinamika Demokrasi Di Indonesia: Studi Kasus Di Kota Pekan Baru - M Rizqi Azmi; Riko Riyanda (UIR Press, 2020)
In the 2019 DPR RI and Provincial, Regency and City (DPRD) DPRD elections, elections were conducted through an open proportional system. In Pekanbaru City, they also feel the same enthusiasm, proportional euphoria is open to election participants. However, this system also contains weaknesses according to the theory, including: Voters' political participation is damaged by political pragmatism in competing for votes so that on the one hand money politics or vote buying and selling are more prevalent, on the other hand political costs are getting more expensive, which encourages the people to corruption. Second, political parties are still dominated by a handful of people who created Politic Oligarch. From the results of the study, it shows that party elites and the voting community in Pekanbaru prefer an open proportional system in the 2019 legislative elections compared to closed proportional ones, there are several considerations such as: (1) An open proportional system is fair enough for legislative competition and can increase transparency in Elections. (2) With an open proportion, it can educate voters through campaign programs. (3) By using any system, the space for political money will always be open. (4) Lower serial numbers still have the opportunity to gain votes. (5) The open proportional system further legitimizes the people's sovereignty in the closed proportional area. (6) The open proportional system further increases voter participation.